A comparison of numerical simulation methods analyzing the performance of a ground-coupled heat pump system. (28th May 2018) - Zarrella, Angelo; Zecchin, Roberto; Pasquier, Philippe; Guzzon, Diego; De Carli, Michele; Emmi, Giuseppe; Quaggia, Michele
Abstract : Ground-coupled heat pumps are increasingly being utilized to heat and cool buildings. Although it is difficult to size and to predict their behavior and performance, their design can be optimized via simulations. EnergyPlus is a popular energy simulation program for modeling building heating and other energy flows and, since it is organized to consider borehole heat exchangers via the well-known g-functions approach, it can be used advantageously for that purpose. The Capacity Resistance Model is another recent numerical simulation tool devoted to ground and borehole heat exchangers. In this work, two methods to calculate the g-fucntions were analyzed, using as case-study a real office building, whose imbalance between the heat extracted and injected into the ground was found to be appreciable. The energy imbalance involves a ground temperature drift affecting the system efficiency. The results of the EnergyPlus g-functions and the Capacity Resistance Model model approaches were compared. The capacity of the two methodologies to accurately simulate this phenomenon were analysed also with reference to the available building's long-term monitoring data. The analysis showed the importance of using g-functions suitable to reflect the layout of the borehole field, in order to correctly evaluate the energy performance of the entire ground source heat pump system.